Production of some bakery products as blends intended for sensitive persons to gluten - Hammad, A. A.; Abo-Elnaga, M. M.; Abdalla, S. H. (2007)
Celiac disease (C. D.), the most common form of malabsorption in Europe, as the result of intestinal mucosal damage caused in susceptible subjects to the gluten content of some cereals such as wheat.
Includes references.
Summary in Arabic.
1
Keywords: Baked products; Gluten; Celiac disease; Celiac disease in children; Rice flour